Heel riser height and slope gradient influence the kinematics and kinetics of ski mountaineering—A laboratory study - Lasshofer, Michael; Seifert, John; Wörndle, Anna-Maria; Stöggl, Thomas (Frontiers in Sports and Active Living, 2022)
In ski mountaineering, equipment and its interaction with the exercising human plays an important role. The binding, as the crucial connection between boot and ski, must ensure safe fixation during downhill skiing and a free moving heel when walking uphill. Uphill, the binding offers the possibility to adopt the height of the heel (riser height) to personal preferences and the steepness of the ascent. This possible adjustment and its influence on various biomechanical parameters are the focus of this work. For this study, 19 male leisure ski mountaineers were tested on a treadmill, ascending at a fixed submaximal speed (3.9 ± 0.4 km·h−1) at 8, 16, and 24% gradient and with three heel riser heights, low (0 cm), medium (3.0 cm) and high (5.3 cm). The applied biomechanical measurement systems included a 3D motion capture system in sagittal plane, pressure insoles, a with strain gauges instrumented pole, spirometry and a comfort scale. Step length and step frequency were influenced by the riser height and the gradient (p ≤ 0.001). The high riser height decreased the step length by 5% compared to the low riser height over all tested gradients, while steps were 9.2% longer at the 24% gradient compared to the 8% gradient over all three riser heights. The high riser height revealed a force impulse of the pole 13% lower than using the low riser height (p < 0.001). Additionally, the high riser height reduced the range of motion of the knee joint and the ankle joint compared to the low riser height (p < 0.001). Therefore, advantageous settings can be derived, with the low riser height creating proper range of motion for ankle, knee and hip joint and higher propulsion via the pole at 8%, while higher riser heights like the medium setting do so at steeper gradients. These findings are in line with the conducted comfort scale. We would not recommend the highest riser height for the analyzed gradients in this study, but it might be an appropriate choice for higher gradients.